Editor-in-chief’s Editorial. Full conference proceedings – for the first time in FormAkademisk - Reitan, Janne Beate (FormAkademisk, 2021)
In the current special issue, FormAkademisk, for the first time, will publish the complete proceedings of a conference. We are proud to announce that this will be the 1st Biennial International Conference for the Craft Sciences (BICCS, 2021), held on the 4–6th of May 2021 online, initiated by the Craft Laboratory, affiliated with the Department of Conservation, University of Gothenburg, Sweden. As a result of the Covid-19 situation, the conference will be held completely online. The special editor of this issue is Camilla Groth, who is also a member of our main editorial team. In addition, Tina Westerlund and Gunnar Almevik are members of this special issue editorial team (Groth et al., 2021).